The Effect of Combined Exercise on Bone Mineral Density of Premenopausal Females - Safoura Ghasemi; Heydar Sadeghi; Ahmad Tahamoli Roudsari; Zahra Basiri (Hamadan University of Medical Sciences, 2016)
Background and Objectives: The best way to prevent osteoporosis, at old age is to prevent bone loss and at young age is trying to keep bones healthy, therefore the aim of this study was to determine the effect of combined exercise on bone mineral density of premenopausal females. Materials and Methods: This semi-experimental study was conducted among 20 premenopausal females between 40 and 45 years old, which were randomly assigned to two groups (experimental and control groups) in Hamadan city, during year 2016. The experimental group completed a 12-week combined exercise-training program (6 weeks in water and 6 weeks on land), three times a week and 70 minutes per session. Before and after the 12 weeks, femoral bone mineral density in all samples was measured by DEXA bone mineral densitometry. Data were analyzed with the SPSS 21 software using descriptive and inferential statistics, such as independent and paired t-test, and Analysis of Covariance (ANCOVA). Results: Bone mineral density of femoral neck and total hip of the experimental group, had significant differences with corresponding areas of the control group (P <0.05). In other words, the results revealed that 12 weeks of combined exercise increases femoral bone mineral density in the experimental group with a significant decrease in the control group. Conclusions: According to the results, to prevent a decrease in bone mineral density during the menopausal period, combined exercises are recommended for females at this age.